Cocreating a programme to prevent injuries and improve performance in Australian Police Force recruits: consumer, industry partner and researcher involvement protocol - Evert Verhagen; Myles Calder Murphy; Joanne Kemp; Andrea Mosler; Caroline Jones; Simone Radavelli-Bagatini; Andrea Bruder; Jonathan Hodgson; Joletta Belton; Garth Allen; Vanessa R Sutton; Debra Langridge (BMJ Open Sport & Exercise Medicine)
We are conducting a research program to cocreate, implement and evaluate an injury prevention intervention for the Western Australia (WA) Police Force Recruit Training Academy. This programme of research has three primary phases: (1) cocreate an injury prevention intervention for the WA Police Force with WA Force recruits, WA Police Force staff, health professionals and injury prevention experts, (2) implement the injury prevention intervention into WA Police Force Recruit training and (3) evaluate the reach, effectiveness, adoption, implementation and maintenance of the injury prevention intervention. Our research programme includes the involvement of consumers, industry partners and researchers. To ensure collaboration and to measure our consumer, industry partner and researcher involvement, we have developed a protocol, including qualitative and quantitative evaluation, to address potential barriers to involvement. Thus, this protocol details our consumer, industry partner and researcher involvement plan across all three phases of this 5-year project and how we will evaluate their experience and influence. Our primary objective is to ensure meaningful consumer, industry partner and researcher involvement at all stages of the research process and evaluate how the research programme was influenced by consumer, industry partner and researcher involvement.